The Effect of Bank Image and Trust on Loyality Mediated by Customer Satisfaction - Sumadi, Sumadi; Soliha, Euis (Department of Management, Faculty of Economics and Business, Universitas Negeri Semarang, 2015)
The purpose of this study is to analyze the effect of the banks image and trust on customer satisfaction, as well as the effect of the image of the bank, trust, and satisfaction on customer loyalty. The study used sample of 100 people who were taken by purposive sampling technique. This research utilized multiple linear regression analysis and path analysis. Based on the hypothesis test, the results show that the image of the bank was significantly has positive effect on customer satisfaction, but trust has no significant effect on customer satisfaction. In addition, the banks image has no significant effect on customer loyalty. Moreover, trust and customer satisfaction significantly have positive effect on customer loyalty. Mediation test shows that customer satisfaction mediates the effect of the banks image on customer loyalty and customer satisfaction does not mediate trust on customer loyalty.Â